Synergistic Antitumor Effects of Anlotinib Combined with Oral 5-Fluorouracil/S-1 via Inhibiting Src/AKT Signaling Pathway in Small-Cell Lung Cancer - Xinhang Xia; Wenhu Pi; Yanli Lan; Xiaomai Wu; Dongqing Lv; Yinnan Meng; Haihua Yang; Wei Wang (Analytical Cellular Pathology)
Background. Small-molecule tyrosine inhibitor anlotinib which developed in China has been approved as a third-line treatment for patients with small-cell lung cancer (SCLC). Our previous clinical study found that anlotinib combined with S-1 has better short-term ORR than the single-agent anlotinib of SCLC and other small-molecule vascular targeted drug therapies in the treatment of SCLC. However, the molecular mechanism of those effect remains unclear. Methods. SCLC cell line H446 was treated with either anlotinib, 5-FU alone, or combination. The cellular effects including cell viability, cell apoptosis, cell cycle, cell migration, and invasion were explored to evaluate the cell proliferation level. Western blot was performed to determine the protein levels of the combined action of the two drugs. The xenograft mouse model was established by injection of H446 cells into mouse, and the animals were randomized and assigned for the drug treatments. Body weights and tumor sizes were recorded. WB was conducted using tumor tissues. All data were collected and statistically analyzed using t-test to reveal the underlying molecular mechanism. Results. When anlotinib was combined with 5-FU, the IC50 value of cells was significantly reduced. And apoptosis, cell cycle arrest, and cell motility rates were stronger when anlotinib combined with 5-FU than in the anlotinib or 5-FU alone. In H446 cell-derived xenograft mouse model, tumor volumes were significantly decreased in Anlo/5-FU combination group than anlotinib or 5-FU alone group. Western blot showed the decreasing expression of p-Src/p-AKT in the Anlo/5-FU group. Conclusion. Our data revealed that the treatment of combination of antitumor angiogenesis agent anlotinib with chemotherapy drug 5-FU may have synergistic cytotoxicity to SCLC in vitro and in vivo. This treatment modality reduced cell proliferation and migration via Src/AKT pathway. This new strategy may be a promising treatment for SCLC but needs to be confirmed in future clinical trials.